Komunikasi Lingkungan Berbasis Kearifan Lokal dalam Upaya Pelestarian Sumber Air di Desa Pedawa - Made Dwi Pradnyana Putra; Sri Hastjarjo; Ign. Agung Satyawan (Jurnal Ilmu Sosial dan Humaniora, 2025)
The existence of water and culture in Pedawa Village are two interrelated things. The importance of the existence of various water sources for village traditions and rituals becomes a problem when the existence of water sources is not adequately maintained. The problems that arise include the lack of water availability and the hampered implementation of rituals in Pedawa Village. The Kayoman Community is one of the communities that focuses on efforts to conserve water sources in Pedawa Village by conducting environmental communication based on local wisdom. This study aims to determine environmental communication based on local wisdom carried out by the Kayoman Community in overcoming water source problems in Pedawa Village. The method used in this study is qualitative. Data was collected through in-depth interviews, document studies, and documentation. The results of this study indicate that Kayoman carries out four stages in conducting environmental communication, including identifying problems and communication objectives, selecting media and communication channels, developing messages and producing media, and the program and communication evaluation stage. The environmental message emphasized by Kayoman is the importance of water for village traditions and culture. The environmental message is conveyed through various programs designed by Kayoman, including the tengetisasi program, the one-marriage one-tree program, the Kayoman foster program, and the making of short films.